FOTOBAZIRANE DOKUMENTACIJSKE METODE U PODVODNOJ ARHEOLOGIJI NA PRIMJERU BRODOLOMA KOD OTOKA VERUDA BLIZU PULE. - BEKIĆ, Luka; SCHOLZ, Roman; PEŠIĆ, Mladen (Histria Archaeologica, 2017)
The island of Veruda - also referred to colloquially as Monks' Island - is a favourite holiday destination for the inhabitants of the Croatian city of Pula. Archaeologists with the International Centre for Underwater Archaeology in Zadar (ICUA) surveyed the Veruda area in the autumn of 2013. They identified a mound of ballast stones that appeared to be from a shipwreck. Small archaeological artefacts and the remains of the structure of a wooden vessel were discovered under the ballast stones. By 2016 ICUA Zadar and the German Archaeological Institute (DAI) had jointly initiated the Veruda excavation project. An entirely novel system of digital photogrammetry documentation was developed and used during the excavation in the spring of 2016. In this manner the complete wooden structure was revealed and a very precise 3D model and drawings were produced. Many artefacts were recovered in the course of the excavation, and it appears that the ship carried a cargo of scrap metal, mostly smelted tin and copper and some copper and bronze intermediate products. A few small sherds of post-medieval pottery and glass can be dated to the second half of the sixteenth and early seventeenth century.